Dampak geopolitik pada aliran investasi di pasar modal pada 2022 sampai dengan 2024 - Vitaloka, Eka Dyah (Maliki Interdisciplinary Journal, 2025)
Geopolitics has a significant impact on the flow of investment in global markets, especially between 2022 and 2025. The uncertainties arising from conflicts between countries, economic sanctions, protectionist policies, and changes in global alliances greatly influence how investors choose where to invest their money. The aim of this research is to examine how geopolitical dynamics affect investment movements in the market during this period, as well as to identify the sectors that are impacted and the strategies used to address these issues. The method applied in this study is a literature review with a descriptive-qualitative approach, which observes academic literature and policy reports related to geopolitics, economics, and investment. The results of the analysis indicate that the increasing geopolitical tensions around the world are causing the markets to become more unstable and triggering a shift in investment towards safer assets such as gold and bonds. Conversely, the renewable energy sector and technology are receiving more investment in reaction to the changes occurring globally. Heading into 2025, the implementation of portfolio diversification strategies and adjustments in local policies demonstrate greater resilience in the capital markets, although there are still risks from global uncertainties that need to be watched.